Diagnostic test decision for suppliers in cruise-building supply chain with information asymmetry. (August 2021) - Liu, Bin; Liu, Naimeng; Chen, Yuting
Abstract: To solve the potential supply disruption in cruise-building supply chain, this study explores a supply system consisting of a monopoly supplier, a new entrant supplier, and a cruise-building manufacturer. A two-step option contract including diagnostic test and process improvement is designed to solve the order quantity allocation and to avoid supply disruption. The analysis combines the decision tree with the principal-agent model under information asymmetry. The result shows that the cruise-building manufacturer would like to allocate more orders to the unreliable supplier who implements process improvement. In the end, the detailed numerical analysis is implemented to justify the proposal.